Relationship Between The Use Of Mobile Online Jaminan Kesehatan Nasional (JKN) Outpatients and Patient Waiting Time Satisfaction at Grandmed Hospital Lubuk Pakam in 2025 - Sitepu, Agustatius (JURNAL KESMAS DAN GIZI (JKG), 2025)
Patient comfort during the service process will increase satisfaction. One of the patient dissatisfaction is in the registration system.. The research method used is quantitative descriptive with a cross-sectional design. The population in this study were all outpatients at the Outpatient Registration Center of Grandmed Hospital (RSGM) Lubuk Pakam as many as 124 people with a purposive sampling data collection technique. Data collection was carried out by providing questionnaires. The results of the study showed that the use of online registration using the National Health Insurance  mobile in the good category was 56.5%. Patient satisfaction in the satisfied category was 52.4%. The results of the analysis using the chi-square test found that there was a significant relationship between the use of online registration using the National Health Insurance mobile for outpatients and patient waiting time satisfaction with a value of p (= 0.037) <α (= 0.05). For Grandmed Lubuk Pakam Hospital, in order to design an online registration system that is directly integrated with the treatment polyclinic and patients can make reservations the day before.